Dangerousness Index in Forensic Psychiatric Examination: A Tool for Aiding Medical Decision Regarding the Risk of Antisocial Acts - Daniela Margareta Varga; Florica Voiță-Mekeres; Gabriel Mihai Mekeres; Călin David Buzlea; Lavinia Davidescu; Camelia Liana Buhas (Diagnostics)
Background and Objectives: The assessment of dangerousness and risk of recidivism are crucial aspects of forensic psychiatric evaluations, influencing therapeutic and security measures. This study aimed to develop and validate a new tool, the Dangerousness Index in Forensic Psychiatry (IPPML), following a psychometric scale construction methodology. Materials and Methods: The sample consisted of 261 participants (157 males, 104 females) aged 19–75 years, divided into an experimental group (n = 126) with a history of forensic psychiatric examination and a control group (n = 135) diagnosed with schizophrenia. Results: Exploratory factor analysis revealed two factors, Performance and Social, explaining 45.55% of the data variance. The IPPML demonstrated adequate internal consistency (α = 0.881) for the entire sample, with Factor 1 showing strong consistency (α = 0.896) and Factor 2 exhibiting acceptable consistency (α = 0.628). Reliability ranged from 89.6% to 62.8% when administered to participants with psychoses undergoing forensic psychiatric evaluation, decreasing to 42.5% for legally evaluated patients and increasing from 58.7% to 84.3% for participants with schizophrenia without forensic psychiatric evaluation. Discriminant validity analysis indicated higher psychiatric dangerousness with forensic implications in males. Conclusions: The IPPML shows promise as a tool for assessing dangerousness in forensic psychiatry and aiding medical decision-making regarding the risk of antisocial and potentially harmful acts.